ASSESSING STUDENTS’ HIGHER-ORDER THINKING SKILLS USING A TWO-TIER MULTIPLE CHOICE TEST - Tiara Lestari Paembonan; Awal Mulia Rejeki Tumanggor; Varisky Abraham Dumanaw; Kartyka Nababan; Winda Lidia Lumbantobing (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This quantitative research focuses on defining the profile of students’ Higher Order Thinking Skills (HOTS) using Two-Tier Multiple Choice Test (TTMCT) instrument. The research carried out in SMAN 2 Toraja Utara, Indonesia. From the entire 11th grade science, 109 students were chosen as participant by purposive sampling. TTMCT consisting of 15 questions about acid base concepts with the cognitive domains of analyzing (C4 and evaluating (C5) was used. Before its implementation, the test underwent a rigorous validation and reliability process. The validation provided confidence in the instrument's ability to effectively measure the intended variables and The Cronbach's alpha coefficient of this instrument is 0.71. This study presents two comprehensive results: firstly, students’ HOTS profile is dominated in good category with an average score of 63.83, and secondly, the comparison of cognitive level: analyzing (C4) with the mean percentage is 71.32% then evaluating (C5) cognitive level with the mean percentage is 60.80%.